The Lock-in Effects of Part-Time Unemployment Benefits - Helène Benghalem; Pierre Cahuc; Pierre Villedieu (Institute of Labor Economics (IZA), 2021)
We ran a large randomized controlled experiment among about 150,000 recipients of unemployment benefits insurance in France in order to evaluate the impact of part-time unemployment benefits. We took advantage of the lack of knowledge of job seekers regarding this program and sent emails presenting the program. The information provision had a significant positive impact on the propensity to work while on claim, but reduced the unemployment exit rate, showing important lock-in effects into unemployment associated with part-time unemployment benefits. The importance of these lock-in effects implies that decreasing the marginal tax rate on earnings from work while on claim in the neighborhood of its current level does not increase labor supply and increases the expenditure net of taxes of the unemployment insurance agency.
Keywords: H5; J64; J65; 330; unemployment insurance; part-time unemployment benefits; lock-in effects; unemployment duration